Imaging techniques for diffuse myocardial fibrosis as a marker of high cardiovascular risk in young patients with type 1 diabetes mellitus - Oksana I. Vengrzhinovskaya; Irina Z. Bondarenko; Olga A. Shatskaia; Natalia V. Tarbaeva; Anastasya Iu. Korneluk; Victor Iu. Kalashnikov; Marina V. Shestakova; Natalia G. Mokrysheva (Терапевтический архив)
Background. Type 1 diabetes mellitus (DM 1) disrupts all types of metabolism, especially carbohydrate and lipid ones, leading to many complications. The most serious DM complication is damage to the cardiovascular system (CVS). Prolonged preclinical changes precede the development of pathological processes in the CVS. One of the earliest manifestations of cardiovascular system dysfunction is myocardial remodeling. In patients with DM 1, myocardial remodeling is diagnosed using echocardiography. However, the examination algorithm does not include echocardiography for young patients with DM 1 without evident cardiovascular diseases (CVD). The state of the heart's extracellular matrix and the presence of fibrotic changes in it are actively studied as a marker of changes in the CVS at the preclinical stage. Assessment of the presence of fibrosis foci is available during echocardiography; however, it is generally relevant for patients with DM 1 with pre-existing CVD. The initial formation of diffuse fibrosis (DF) of the myocardium in patients with DM without diagnosed CVD can be verified by magnetic resonance imaging (MRI) of the heart. Given that DF increases the risk of life-threatening arrhythmias and significantly increases the risk of sudden cardiac death in young patients with DM 1, it is necessary to revise the strategy of primary prevention of CVD for patients in this population.